2020
DOI: 10.1101/2020.10.07.329607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RAL GTPases mediate EGFR-driven intestinal stem cell hyperproliferation and tumourigenesis

Abstract: SummaryRAS-like (RAL) GTPases function in Wnt signalling-dependent intestinal stem cell proliferation and regeneration. Whether RAL proteins work as canonical RAS effectors in the intestine, and the mechanisms of how they contribute to tumorigenesis remain unclear. Here, we show that RAL GTPases are necessary and sufficient to activate EGFR/MAPK signalling in the intestine. We identify non-canonical roles of RAL GTPases, not as RAS effectors, but rather by acting upstream of RAS activation via induction of EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 113 publications
(124 reference statements)
0
1
1
Order By: Relevance
“…Our ndings are dissimilar from those reported in three recent studies where RALA and RALB were found to play similar roles in BC cell line models [20,21] or transient silencing of RALB was found to decrease BC cell line invasion [22]. In silico analyses utilizing the large TCGA and METABRIC breast cancer patient gene expression databases uncovered paradoxical associations between survival and RALA and RALB expression in support of our in vitro and in vivo ndings.…”
Section: Introductioncontrasting
confidence: 99%
“…Our ndings are dissimilar from those reported in three recent studies where RALA and RALB were found to play similar roles in BC cell line models [20,21] or transient silencing of RALB was found to decrease BC cell line invasion [22]. In silico analyses utilizing the large TCGA and METABRIC breast cancer patient gene expression databases uncovered paradoxical associations between survival and RALA and RALB expression in support of our in vitro and in vivo ndings.…”
Section: Introductioncontrasting
confidence: 99%
“…Upon tissue damage, internalization of the BMP receptor, Tkv, in ISCs requires Awd, a facilitator of dynamin endocytic function; this promotes Mad activation driving ISC return to quiescence [33]. Similarly, endocytosis of the Wnt receptor (Fz3) and EGFR is regulated by the RalA GTPase, which is essential for the regenerative response of ISCs after damage [34,35].…”
Section: Cell-autonomous Regulation Of Proliferationmentioning
confidence: 99%